2009
DOI: 10.1111/j.1600-0838.2009.00890.x
|View full text |Cite
|
Sign up to set email alerts
|

The facilitative nature of avoidance coping within sports injury rehabilitation

Abstract: Avoidance coping has commonly been reported within literature to be a debilitative process. However, in situations where goal attainment is reduced or eradicated avoidance coping strategies appear to have some benefit. The aim of this study was to identify the role of avoidance coping within the sports injury rehabilitation setting. A mixed methodological approach was utilized with four professional male rugby union players, concurrent with their rehabilitation from anterior cruciate ligament (ACL) surgery. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 29 publications
4
41
1
1
Order By: Relevance
“…In line with coping strategies, Carson and Polman (2010) showed that behavioral as well as cognitive avoidance coping strategies were used equally by the professional rugby players in this study, and that these strategies had positive short-and long-term effects. A common type of strategy was the use of both behavioral (e.g., performing a new hobby) and cognitive (e.g., refusing to watch games) distraction coping.…”
Section: Behaviorsupporting
confidence: 59%
“…In line with coping strategies, Carson and Polman (2010) showed that behavioral as well as cognitive avoidance coping strategies were used equally by the professional rugby players in this study, and that these strategies had positive short-and long-term effects. A common type of strategy was the use of both behavioral (e.g., performing a new hobby) and cognitive (e.g., refusing to watch games) distraction coping.…”
Section: Behaviorsupporting
confidence: 59%
“…Avoidance focused coping strategies were suggested as being both facilitative47 and also debilitative 41 45. A mixed-method study47 of elite professional rugby players found that behavioural and cognitive avoidance coping strategies enhanced perceptions of recovery.…”
Section: Resultsmentioning
confidence: 99%
“…Avoidance focused coping strategies were suggested as being both facilitative47 and also debilitative 41 45. A mixed-method study47 of elite professional rugby players found that behavioural and cognitive avoidance coping strategies enhanced perceptions of recovery. In contrast two studies credited using avoidance coping with less successful rehabilitation outcomes such as a delay in psychological rehabilitation,45 and associated increase in TNM 41…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have investigated the coping strategies that athletes employ during the injury process using both quantitative instruments (Albinson & Petrie, 2003;Quinn & Fallon, 1999, 2000 and qualitative interviews (Bianco et al, 1999;Carson & Polman, 2010;Ford & Gordon, 1999;Podlog & Eklund, 2006). Injured athletes have used problem-focused coping strategies, such as gathering information on the recovery and rehabilitation processes (Carson & Polman, 2008), instrumental coping (Bianco et al, 1998;Hoar & Flint, 2008;Udry, 1997), and active planning (Hagger et al, 2005;Quinn & Fallon, 1999, 2000.…”
Section: Coping With Athletic Injurymentioning
confidence: 99%